Dynastic Politics in Local Elections from the Perspective of Asabiyyah Theory: A Study on the Pilkada Contestation in Ogan Ilir in 2020 - Padri, Padri; Fikri, Sirajudin (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
The aim to be achieved in this research is to explain the portrait of the political dynasty phenomenon in the 2020 regent election in Ogan Ilir. The method used in this research is qualitative with a descriptive method aimed at getting a clear and real picture of the symptoms in the field as a whole, then express descriptively about political dynasties according to Ashabiyah theory. The results of this research show that political insantia in Ogan Ilir occurred because of the connection between previous leadership and current leadership. One of the distinctive characteristics of the election of Panca to replace Mawardi Yahya was that Mawardi Yahya's term of office could not be continued due to limited regulations, making it easier for the Mawardi Yahya family to be elected, where this could create benefits from the formal authority possessed by Mawardi Yahya. Dynasty politics gives rise to negative speculation in the realm of society where dynastic politics provides easy space for elite groups to make their families become leaders from generation to generation and can easily carry out corruption. According to Ashabiyah theory, it is very important for the ruling group to create strong political stability and maintain its power as long as possible. According to him, it is halal to maintain power in various ways with the noble aim of only maintaining political stability.